Impact of probiotics on shrimp culture practices : A case study - Kunda, Sumanth Kumar; Namburu, Praveen Kumar; Lakshman Raju, M. (Indian Journal of Fisheries, 2014)
A study was conducted to evaluate the impact of use of probiotics in shrimp farming. The study was carried out during 2011 in three mandals (talukas) viz., Pitlavani Palem, Nizampatnam and Karlapalem of Guntur District in Andhra Pradesh. The results of the study revealed that all the shrimp farmers used a variety of commercial probiotics comprising water, feed and soil probiotics. Out of the total farmers surveyed, 44% each used water probiotics while and feed probiotics while 12% of the farmers used soil probiotics. The results showed correlation between use of probiotics and shrimp growth and also indicated that the use of probiotics increased benefits in terms of shrimp survival, reduction in total cost of production, reduction of disease prevalence and improved water quality as well as pond bottom conditions.